MITIGATING SALMONELLA RISKS: PREVENTION, FOOD SAFETY PROTOCOLS, AND HANDLING GUIDELINES - Vickneswari M; Monish Raj R; Vijaya Krishanan; Palthangam Ganesan; Dhiva G S (The Bioscan, 2025)
Salmonella is a leading cause of food borne illness globally, posing significant public health and economic challenges. This paper explores comprehensive strategies to mitigate the risks associated with Salmonella contamination in food systems. It examines the microbiological characteristics of Salmonella, common sources of contamination, and transmission pathways. Emphasis is placed on evidence-based prevention strategies, including hygienic food handling, proper cooking and storage practices, and cross-contamination control. Additionally, the paper reviews regulatory frameworks and food safety protocols, such as Hazard Analysis and Critical Control Points (HACCP), which are critical in managing Salmonella risks across the food supply chain. The goal is to provide actionable guidelines for food industry professionals, public health officials, and consumers to reduce infection rates and enhance food safety.